2020
DOI: 10.1001/jamanetworkopen.2020.22111
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Rural-Urban Differences in Health Care Use and Survival Among Medicare Beneficiaries With Alzheimer Disease and Related Dementia

Abstract: This cohort study uses Medicare claims data from nursing home and home health assessments from all US counties to investigate how health care use and survival compares between individuals with Alzheimer disease and related dementia in rural vs urban settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 48 publications
0
51
0
Order By: Relevance
“…These include the higher prevalence of dementia than urban areas, low dementia screening coverage in rural areas, and results from preliminary studies points out dementia as the most common geriatric problem in rural areas. 9,10,11 We obtained a low sensitivity and high specificity for the AMT questionnaire. This finding was similar to previous studies, which observed a wide sensitivity variation (12.8-99%) but consistently high specificity (84-100%) for AMT.…”
Section: Discussionmentioning
confidence: 89%
“…These include the higher prevalence of dementia than urban areas, low dementia screening coverage in rural areas, and results from preliminary studies points out dementia as the most common geriatric problem in rural areas. 9,10,11 We obtained a low sensitivity and high specificity for the AMT questionnaire. This finding was similar to previous studies, which observed a wide sensitivity variation (12.8-99%) but consistently high specificity (84-100%) for AMT.…”
Section: Discussionmentioning
confidence: 89%
“…It should be noted that our study does have some limitations. In particular, previous studies have indicated that risks in addition to genetic risk can lead to AD (Durazzo et al, 2014;Rahman et al, 2020;Thomas et al, 2020). For example, a recent study showed that individuals with diabetes and the ɛ4 allele demonstrated a faster functional decline than those without diabetes (Thomas et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…18 For purposes of this study, three categories are defined: urban, urban-adjacent rural (UAR), and nonurban-adjacent rural (NAR). 19,20 This classification has been commonly used to attribute rurality based on census tract or ZIP Code. 21,22 To validate representativeness of the cohort population with the overall US population, we compared the population percentages for each category in N3C with the US population using public datasets.…”
Section: Cohort Identificationmentioning
confidence: 99%